The Philippines MTB-MLE Program: Reconciling Its Utilitarian and Ideological Rationales - Jerone Avel Cansino (East Asian Journal of Multidisciplinary Research, 2023)
This paper explored the literature on the implementation of "Mother Tongue Based-Multilingual Education" in the Philippines using the Postcolonial lens expressed by Constantino and Osias. It argues that the program is misunderstood among its stakeholders, and there have been lapses in its planning and implementation. This paper attempts to reconcile ideological and pragmatic principles that underly the MTB-MLE program in the Philippines. It was argued that the failure of the program was not due to it being theoretically ungrounded. Still, on the implementation side, as evidenced by the lack of reference materials and instructional materials, the skill gap between the teachers and the necessary language skills is also apparent, aside from the unforeseen challenges concerning the multilingual classroom contexts.